The Influence of Financial Literacy, Financial Technology, and Financial Inclusion on the Performance of Savings and Loan Cooperatives - Gea, Yelda Nispa; Hendrajaya, Hendrajaya (Mahesa Research Center, 2025)
This article aims to analyze the influence of financial literacy, financial technology, and financial inclusion on the performance of savings and loan cooperatives in Ungaran District. This study involved 100 respondents consisting of cooperative managers and members, with data collected through structured questionnaires and analyzed quantitatively using multiple linear regression. The results showed that financial literacy has a significant positive effect on cooperative performance (? = 0.198, p < 0.01), indicating that an increased understanding of financial management and financial products effectively supports better financial decision-making. Financial technology also showed a very significant positive impact (? = 0.586, p < 0.001), indicating that the adoption of digital solutions and fintech innovations drastically improves operational efficiency and service quality. In contrast, the effect of financial inclusion was not significant (? = -0.191, p > 0.05), allegedly caused by obstacles in optimizing service utilization, low levels of member understanding, and regulatory and infrastructure barriers that still need to be improved. These findings imply that increasing literacy and technology adoption are key to improving cooperative performance, while financial inclusion strategies need to be further evaluated. The practical implications of this study encourage cooperatives to conduct regular training, integrate fintech solutions, and develop more holistic inclusion strategies to support competitiveness and sustainability in the digital era.